2016
DOI: 10.1038/srep38943
|View full text |Cite
|
Sign up to set email alerts
|

Association of Bicipital Peritendinous Effusion with Subacromial Impingement: A Dynamic Ultrasonographic Study of 337 Shoulders

Abstract: Bicipital peritendinous effusion (BPE) is the most common biceps tendon abnormality and can be related to various shoulder ultrasonographic findings. Since the association of BPE with subacromial impingement is unclear, our study aimed to explore its association with the dynamic subacromial impingement test during ultrasound (US) imaging. We included 337 shoulders referred for US examinations and quantified the amount of BPE. Effusion more than 1 mm in thickness was considered a positive finding. A comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 23 publications
(60 reference statements)
0
12
0
Order By: Relevance
“…In the standardized training program of MSKUS, the shoulder is usually the first joint to be taught. When physicians start to apply imaging modalities in clinical practice, they find it useful because of the high prevalence of shoulder disorders [24, 25]. Further, the main structures imaged during shoulder examination, such as rotator cuff tendons, are superficial and easily scanned with ultrasonography.…”
Section: Discussionmentioning
confidence: 99%
“…In the standardized training program of MSKUS, the shoulder is usually the first joint to be taught. When physicians start to apply imaging modalities in clinical practice, they find it useful because of the high prevalence of shoulder disorders [24, 25]. Further, the main structures imaged during shoulder examination, such as rotator cuff tendons, are superficial and easily scanned with ultrasonography.…”
Section: Discussionmentioning
confidence: 99%
“…Some well-designed retrospective and prospective researches reported that acquired shoulder disorders can be diagnosed via ultrasound in experienced hands. [ 26 , 27 ] In addition, Chang et al [ 28 ] postulated that ultrasound can also be beneficial in the treatment of adults with shoulder pain as a guide for subacromial corticosteroid injections.…”
Section: Discussionmentioning
confidence: 99%
“…The biceps tendon sheath derives from the extension of the glenohumeral joint capsule; biceps tendon effusion is attributed to intra-articular pathology. 4 Prominent effusion of the glenohumeral joint increases the biceps tendon sheath effusion. 29 In a short-axis scan, effusion surrounding the biceps tendon was considered abnormal (Figure 1D).…”
Section: Ultrasound Parametersmentioning
confidence: 99%